Development of Electronic Teaching Materials Using Flip PDF Professional in Class V Elementary School - Feby Kurniawan; Daharnis; Zelhendri Zen; Yeni Erita (Postgraduate, University of Mataram, 2024)
Flip PDF Professional is software that has the ability to convert PDF documents into digital rotating pages, which enables the creation of interactive learning content with a variety of supporting features. This research includes a type of research and development that develops, produces, validates and tests whether the product is effective or not and can be accounted for. This research uses the ADDIE model where the stages are A (Analysis), D (Design), D (Development), I (Implementation) and E (Evaluation). Based on the results of the validity test of electronic teaching materials using Flip PDF Professional in class V elementary school, the material expert assessment results were 96% in the very valid category, media/design experts were 88% in the very valid category and language experts were 95% in the very valid category. very valid. Meanwhile, the practicality results show very practical criteria after assessing practicality by students with an average score of 92.77% in the very practical category and practicality assessment by teachers with an average score of 86.67% in the very practical category. This shows that electronic teaching materials using Flip PDF Professional in class V elementary schools meet the criteria of being very practical and valid for application in elementary schools.